Psychological Capital as a Predictor of Organizational Citizenship Behaviour in the Personnel and Human Resources Development Agency employees in West Kalimantan - Maulida Rahman, Riki; Endang Kusmaryani, Rosita (Green Publisher Indonesia, 2024)
This research starts from an indication of the low Organizational Citizenship Behavioral (OCB) of government agency employees at the Personnel and Human Resources Development Agency (BKPSDM) in West Kalimantan. Previous research explains that the predictor of employee OCB level is psychological capital. Therefore, this study aims to determine psychological capital as a predictor of organizational citizenship behavior in the Civil Service Agency and Human Resources Development employees in West Kalimantan. This research uses quantitative with ex-post facto type. The sample used was 52 BKPSDM employees in West Kalimantan. The instrument validation technique uses construct validation and previous research reliability. The data analysis technique uses descriptive and inferential analysis consisting of classical assumption tests and hypothesis testing. The results of this study indicate inferential analysis in the simultaneous test (F test) psychological capital variables become predictors of OCB. Then a partial test (T test) the hope dimension had no effect, the optimism dimension had no effect, the resilience dimension had no effect, and the self-efficacy dimension was the only predictor of psychological capital on OCB.